Hybrid SuperHyperSoft Model for Evaluation of Comprehensive Transportation Efficiency: Analysis and Results - Zigeng Wen; Jie Liu; Jianchang Huang (Neutrosophic Sets and Systems)
In this research, we investigate the features of comprehensive transportation efficiency assessment. Optimizing the energy-saving and efficient comprehensive transportation structure is essential to further lowering logistics costs. We evaluate the transportation efficiency using the decision making model based on a set of criteria and alternatives. We used two methods. named BWM and MABAC methods. The BWM is used to compute the criteria weights and the MABAC method is used to rank the alternatives. These methods are used under the neutrosophic set to solve the uncertainty information. These methods are used with SuperHyperSoft to treat various criteria and sub criteria by using a set of sets. Eight criteria and nine alternatives are used in this study. The sensitivity analysis shows the proposed approach rank in stable under different cases. The comparative analysis shows the proposed approach is effective compared to other methods.